2021
DOI: 10.1111/jgh.15529
|View full text |Cite
|
Sign up to set email alerts
|

External validation of blue light imaging (BLI) criteria for the optical characterization of colorectal polyps by endoscopy experts

Abstract: MD and PS has conceptualized and developed the project. KFK has performed the statistical analysis. MD and PS has interpreted and analyzed the results. MD and KFK created tables and figures. MD and PS has written, edited, and revised the manuscript. All authors have reviewed and edited final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In another study, endoscopy experts identified, with the use of the BASIC system, conventional adenoma (vs. non-adenoma) with 94.4% accuracy, 95% sensitivity, 93.8% specificity, 93.8% positive predictive value, and 94.9% negative predictive value. Moreover, the study validated the use of the BASIC classification system to characterize colorectal polyps with >90% accuracy and a high level of interobserver agreement [32].…”
Section: Blue Laser Imaging (Bli)mentioning
confidence: 64%
“…In another study, endoscopy experts identified, with the use of the BASIC system, conventional adenoma (vs. non-adenoma) with 94.4% accuracy, 95% sensitivity, 93.8% specificity, 93.8% positive predictive value, and 94.9% negative predictive value. Moreover, the study validated the use of the BASIC classification system to characterize colorectal polyps with >90% accuracy and a high level of interobserver agreement [32].…”
Section: Blue Laser Imaging (Bli)mentioning
confidence: 64%
“…This requires that in the context of suspected rectosigmoid hyperplastic polyps that are 5 mm or smaller, the technology should provide a negative predictive value (NPV) greater than 90%, when used with high confidence, for adenomatous histology. (45) Examples of IEE classification include the Kudo pit pattern, (41) Sano, (46) NBI International Colorectal Endoscopic, (47) Japan NBI Expert Team (48) and BLI Adenoma Serrated International Classification (49) systems.…”
Section: Computer-aided Diagnosis For Polyp Characterisation During C...mentioning
confidence: 99%
“…Blue light imaging (BLI) is form of digitally enhanced imaging which concentrates and enhances a specific wavelength of light between 410-450 nm, increasing the contrast of superficial micro-vessels and mucosal surface structures (Figure 2 ). BLI uses four independent light-emitting diodes rather than the xenon light used in NBI, which is postulated to improve brightness[ 88 ]. This new technology has not been as extensively studied, however a video-based 2015 study demonstrated improved visibility scores with BLI bright mode compared to WLI according to both expert and non-expert proceduralists[ 89 ].…”
Section: Polyp Detectionmentioning
confidence: 99%